Dose enhancement effects with different size of gold nanoparticles for 6 mv photon beam - Muhammad, Mahfuzah (Universiti Sains Malaysia, 2016)
Gold nanoparticles (AuNPs) have been widely investigated as radiation dose enhancer for radiotherapy due to its intriguing potential in increasing radiotherapy therapeutic efficiency. The applicability of AuNPs depends on many factors including nanoparticles size. In this study, the effects of nanoparticle size on the AuNPs dose enhancement effects were investigated. AuNPs of 5nm and 15 nm were used in this study. The efficacy of both sizes of AuNPs was tested in-vitro using HeLa cell lines. The cells were incubated with the AuNPs and irradiated at different doses with 6 MV photon beam at 100 cm SSD and 10 cm x 10 cm field size. Cell survival curves were obtained from standard clonogenic assay and fitted to the Linear Quadratic (LQ) model using OriginPro 9.2 software. Dose enhancement factor (DEF) and radioparameters were extrapolated and evaluated from the cell survival curve. The results show that 15 nm AuNPs produce better dose enhancement compare to 5 nm of AuNPs. DEF for 15 nm are found to be around 2.2 meanwhile for 5nm is 1.75. The curves also demonstrate steepest slope and small shoulder for larger size AuNPs which indicate increase in biological effects. The LQ parameters such as alpha, beta and alpha/beta ratio are in agreement with the DEF results. Larger size AuNPs produce higher dose enhancement compare to small size of AuNPs which conclude that nanoparticles size is important factor that need to be taken into account for AuNPs to be applied in radiotherapy.